2020
DOI: 10.3389/fpsyg.2020.603420
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Pain Catastrophizing: Putting Pieces Together

Abstract: The present narrative review addresses issues concerning the defining criteria and conceptual underpinnings of pain catastrophizing. To date, the concept of pain catastrophizing has been extensively used in many clinical and experimental contexts and it is considered as one of the most important psychological correlate of pain chronicity and disability. Although its extensive use, we are still facing important problems related to its defining criteria and conceptual understanding. At present, there is no gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 159 publications
(254 reference statements)
2
78
0
Order By: Relevance
“…Furthermore, given the multidimensional nature of pain catastrophizing [ 41 ], it is especially interesting to direct actions towards the specific component involved. As has been pointed out, although pain catastrophizing has been considered as one of the most relevant psychological predictors of chronicity and disability related to pain, there are important problems still remaining in relation to its conceptualization [ 72 ]. Clarifying the construct and analyzing the elements involved in each case is essential for the development of more personalized, and consequently, more effective interventions [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, given the multidimensional nature of pain catastrophizing [ 41 ], it is especially interesting to direct actions towards the specific component involved. As has been pointed out, although pain catastrophizing has been considered as one of the most relevant psychological predictors of chronicity and disability related to pain, there are important problems still remaining in relation to its conceptualization [ 72 ]. Clarifying the construct and analyzing the elements involved in each case is essential for the development of more personalized, and consequently, more effective interventions [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…As has been pointed out, although pain catastrophizing has been considered as one of the most relevant psychological predictors of chronicity and disability related to pain, there are important problems still remaining in relation to its conceptualization [ 72 ]. Clarifying the construct and analyzing the elements involved in each case is essential for the development of more personalized, and consequently, more effective interventions [ 72 ]. This multidimensionality could explain the fact that most interventions aimed at modifying pain catastrophizing produce only modest benefits, unless targeted to people showing high levels of this variable [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data showed that pain cognitions, particularly catastrophizing, strongly influenced pain intensity, pain interference and their relationship (Hirsh et al, 2011 ). Catastrophizing itself is not only dependent on previous painful experiences but can also be influenced by environmental factors (Petrini & Arendt‐Nielsen, 2020 ). During COVID‐19, psychological distress, catastrophizing, sedentarism and social isolation may all contribute to swell the burden of pain (Alzahrani et al, 2019 ; Hammig, 2019 ; Joseph et al, 2020 ; Zhaoyang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical point of view our results questioned the magnification component of pain catastrophizing, which is in line with a recent psychometric study by Cook and colleagues (2021). Identifying the key elements of pain catastrophizing is not just a methodological question but a more basic conceptual one (Petrini and Arendt-Nielsen, 2020), pointing out the need for a more cohesive understanding of pain catastrophizing.…”
Section: Limitationsmentioning
confidence: 99%